2016
DOI: 10.1186/s12884-016-1108-4
|View full text |Cite
|
Sign up to set email alerts
|

Timely initiation of breastfeeding and associated factors among mothers in Motta town, East Gojjam zone, Amhara regional state, Ethiopia, 2015: a cross-sectional study

Abstract: BackgroundTimely initiation of breastfeeding within one hour after birth and exclusive breastfeeding is recommended for the first six months of infant life along with continuation of breastfeeding up to two years. Timely initiation of breastfeeding has the potential to prevent 22 % of neonatal deaths. The objective of this study was to assess timely initiation of breastfeeding and associated factors among mothers who have infants less than six months of age in Motta town, East Gojjam, Amhara Regional State, Et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
65
3
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(101 citation statements)
references
References 13 publications
28
65
3
5
Order By: Relevance
“…A mother who gave birth via vaginal delivery was 6.67 times more likely to initiate breastfeeding within one hour than those gave birth via cesarean section. This finding is in line with studies done in Bahiradr (15) and Motta (17) . This may be due to recovery for the mother after cesarean which make it difficult to initiate breastfeeding early.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…A mother who gave birth via vaginal delivery was 6.67 times more likely to initiate breastfeeding within one hour than those gave birth via cesarean section. This finding is in line with studies done in Bahiradr (15) and Motta (17) . This may be due to recovery for the mother after cesarean which make it difficult to initiate breastfeeding early.…”
Section: Discussionsupporting
confidence: 93%
“…The current study showed that mothers who were counseled during antenatal visits were 4.67 times more likely to initiate timely breastfeeding than those who were not counseled during antenatal visits. This finding is consistent with studies done in Ethiopia; Bahiradr (15) and Motta (17) This may be due to mothers who had antenatal visits receive enough information about the importance of early initiation of breastfeeding and have also adequate knowledge about breastfeeding, which may lead to early initiation of breastfeeding compared to women who were not counseled.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The current study finding revealed that early initiation of breastfeeding in West Belessa district was 77.7% (95%CI, 74.3-81.0). This finding is similar to the study Debre Tabor which is 76.8%(26), Motta 78.8% (27), Dembecha District 73.1% (28), and EDHS 2016 74.3% (18). The possible correspondence might be most of the previous and current studies might similar study settings and target populations.…”
Section: Discussionsupporting
confidence: 90%
“…Egger's regression test for funnel plot asymmetry was not significant (z = 0.28, p = 0.78). Likewise, 12 studies 22,23,25,26,[28][29][30][31][32][33]35,53 reported the association between TIBF and ANC in 11,712 mothers (Table 1B). The pooled OR of ANC was 1.61 (95% CI 1.01 -2.57) ( figure 3).…”
Section: Timely Initiation Of Breastfeeding (Tibf)mentioning
confidence: 84%